Prospek Usaha Pembuatan Batu Bata Dalam Kesejahteraan Karyawan Menurut Etika Bisnis Islam : (Studi Pada Pengusaha Batu Bata Di Desa Lingkarnago Kelurahan Sungai Bengkal - Kabupaten Tebo) - Nizammuddin Silmi; Titin Agustin Nengsih; Muhammad Subhan (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This thesis discusses the prospect of brick-making business in employee welfare according to Islamic business ethics (study on brick entrepreneurs in Lingkarnago Village, Bengkal River-Tebo Regency). This study aims to analyze the prospects of brick-making business in employee welfare according to Islamic business ethics. This research is a type of descriptive qualitative research. The research location is located in Lingkarnago Village, Bengkal River Whole-Tebo Regency. Data are obtained through observation, interviews, and documentation. Furthermore, data collection techniques are analyzed by data reduction, data presentation, and conclusions. The results of this study show that the prospect of brick making business in Lingkarnago Village has good and good prospects in the brick industry. With the brick making business industry in Lingkarnago Village, it can open up job opportunities for the surrounding community, namely increasing income for both labor and brick craftsmen who are able to improve economic welfare in the local community. The brick business in Lingkarnago Village has applied Islamic business ethics well, namely, providing time for worship for employees, providing wages to employees on time, accepting and being responsible if consumers complain, and applying principles by explaining the products to be sold. Keywords: Brick Business Prospects, Employee Welfare, Islamic Business Ethics